2020
DOI: 10.1186/s12885-020-6561-9
|View full text |Cite
|
Sign up to set email alerts
|

Coffee drinking and cancer risk: an umbrella review of meta-analyses of observational studies

Abstract: Background: Epidemiological studies on the association between coffee intake and cancer risk have yielded inconsistent results. To summarize and appraise the quality of the current evidence, we conducted an umbrella review of existing findings from meta-analyses of observational studies. Methods: We searched PubMed, Embase, Web of Science and the Cochrane database to obtain systematic reviews and meta-analyses of associations between coffee intake and cancer incidence. For each association, we estimated the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 33 publications
4
34
0
1
Order By: Relevance
“…Several investigations revealed that tea and coffee may have different effects in some cancer types. It is noticeable that coffee may increase a risk in certain types of cancer (bladder cancer, lung cancer, and childhood leukemia) in line with the finding from aforementioned studies which examined effects of either tea or coffee, individually [ 93 ].…”
Section: Anti-cancer Effects Of Coffeesupporting
confidence: 69%
See 2 more Smart Citations
“…Several investigations revealed that tea and coffee may have different effects in some cancer types. It is noticeable that coffee may increase a risk in certain types of cancer (bladder cancer, lung cancer, and childhood leukemia) in line with the finding from aforementioned studies which examined effects of either tea or coffee, individually [ 93 ].…”
Section: Anti-cancer Effects Of Coffeesupporting
confidence: 69%
“…In addition, a recent meta-analysis of observational studies on associations between coffee intake and 26 different cancers including 364,749 cancer cases provided evidence to show that coffee intake is inversely associated with endometrial cancer, liver cancer, melanoma, oral cancer, and oral/pharyngeal cancer [ 93 ]. Additional evidence was also obtained to suggest the reduced risk of cancers of the mouth, pharynx and larynx, and skin cancer.…”
Section: Anti-cancer Effects Of Coffeementioning
confidence: 99%
See 1 more Smart Citation
“…This inverse relation may simply be due to the fact that subjects with digestive disorders, chronic liver diseases, and cirrhosis reduce spontaneously their coffee consumption, because of impairment in caffeine metabolism (reverse causation bias) [71,72] . Indeed, systemic caffeine clearance correlates with liver disfunction, and its measurement, even in saliva, has been suggested as a non-invasive test to evaluate residual liver function in patients with chronic liver disease [73][74][75][76][77][78] . Moreover, in compensated cirrhotics, some authors have reported that the total overnight salivary caffeine assessment could be useful in distinguishing between viral and metabolic etiology [77] .…”
Section: Limitations In the Interpretation Of Epidemiological Studiesmentioning
confidence: 99%
“…As pancreatic cancer is notorious for having a poor prognosis (Bray et al, 2018), finding modifiable risk factors is paramount. While coffee is a popular beverage globally, Zhao et al, (2020) concluded that 'there is highly suggestive evidence for an inverse association between coffee intake and risk of liver and endometrial cancer.' But Tsai and Chang (2019) concluded that 'the association between coffee and pancreatic cancer is unclear.'…”
Section: Introductionmentioning
confidence: 99%